The becoming of a hero: identity conflicts in contemporary Hindi cinema : the protogonist as a site for political, social and religious conflicts - Bivalkar, Pradnya (Eberhard Karls Universität Tübingen, Tübingen Library Publishing, 2023)
Identity conflicts, a prominent feature of our times, a phenomenon of belonging somewhere yet belonging nowhere, are increasingly finding their way into cinema. This book looks at the representations of identity conflicts in India on the canvas of Indian cinema, connecting them with broader socio-political developments in contemporary India. Starting with the historical background of how political developments in Europe like the emergence of Nation states, secularism, modernity influenced socio-political developments in India in the past century, the book looks at how those developments have shaped modern India. While looking at the cinematic representations of a variety of identity conflicts through the lens of cultural and political analysis, it provides insights into how the construct of an Identity and the inherent conflicts associated with it evolve and manifest themselves through the medium of a film.